2013
DOI: 10.1007/s11033-013-2620-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative gene expression analysis in a highly anthocyanin pigmented mutant of colorless chrysanthemum

Abstract: In this study, we investigated differentially expressed genes between the original chrysanthemum cultivar 'Argus' with white flower color and its gamma-ray irradiated mutant 'ARTI-purple' with purple flower color. The expression levels of anthocyanin biosynthetic genes were not associated with anthocyanin accumulations of Argus and ARTI-purple. Expressed sequence tags (ESTs) analysis was performed to identify a novel cDNAs encoding enzymes of specific plant metabolic pathways and the biological effects of gamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…However, analysis of anthocyanin content using a spectrophotometer revealed that anthocyanin contents in transgenic lines of the cultivars were significantly higher than those in the controls. Thus, anthocyanin accumulation in the cultivars was correlated with the expression pattern of biosynthetic genes as reported by the researchers (Chen et al 2012 ; He et al 2013 ; Sung et al 2013 ), but anthocyanin content produced by RsMYB1 seemed to be genotype-dependent because enhancement of anthocyanin contents in cultivars ‘Peach ND’ and ‘Vivid Scarlet’ seemed to be higher than that in cultivar ‘Peach Red’ (Fig. 5 ).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…However, analysis of anthocyanin content using a spectrophotometer revealed that anthocyanin contents in transgenic lines of the cultivars were significantly higher than those in the controls. Thus, anthocyanin accumulation in the cultivars was correlated with the expression pattern of biosynthetic genes as reported by the researchers (Chen et al 2012 ; He et al 2013 ; Sung et al 2013 ), but anthocyanin content produced by RsMYB1 seemed to be genotype-dependent because enhancement of anthocyanin contents in cultivars ‘Peach ND’ and ‘Vivid Scarlet’ seemed to be higher than that in cultivar ‘Peach Red’ (Fig. 5 ).…”
Section: Discussionsupporting
confidence: 69%
“…In addition, many researchers have documented that anthocyanin accumulation in chrysanthemum correlated with the expression pattern of biosynthetic genes (Chen et al 2012 ; He et al 2013 ; Sung et al 2013 ). Since the main anthocyanin biosynthesis pathway in chrysanthemum is the cyanidin-based pathway (He et al 2013 ), CHS , CHI , F3H , DFR , and ANS are considered as five key biosynthetic genes responsible for anthocyanin accumulation in chrysanthemum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the white-flowered mutant lines, reduced expression of genes encoding either enzymes or positive regulators of anthocyanin biosynthesis were observed ( Han et al 2012 ). In the purplish-red-flowered mutant lines, expression of a R2R3-MYB transcription factor (designated CmMYB1) was markedly reduced ( Sung et al 2013 ). Because the amino acid sequence of CmMYB1 showed high similarity to AtMYB4, which are negative regulators of anthocyanin biosynthesis in Arabidopsis ( Jin et al 2000 , Matsui et al 2008 ), the authors suggested that CmMYB1 also acts as a negative regulator of anthocyanin biosynthesis in chrysanthemum ray petals.…”
Section: Pink and Purplish-redmentioning
confidence: 99%
“…Using a purple gamma-ray irradiated mutant 'ARTIpurple', and analyzing expressed sequence tags (ESTs), Sung et al (2013) identified novel cDNAs encoding enzymes of specific plant metabolic pathways that reflect the unique expression caused by gamma-ray mutation -invariably one of the most popular breeding methods. They isolated 796 unigenes from ray florets, some of which were involved in carbohydrate and lipid metabolic pathways, or were transcription factors or signal transduction genes.…”
Section: Advances In the Understanding Of Flowering And Flowering-relmentioning
confidence: 99%